A robust adaptive fuzzy variable structure tracking control for the wheeled mobile robot: Simulation and experimental results. (July 2017) - Begnini, Mauricio; Bertol, Douglas Wildgrube; Martins, Nardênio Almeida
Abstract: In this paper an adaptive fuzzy variable structure control (kinematic control) integrated with a proportional plus derivative control (dynamic control) is proposed as a robust solution to the trajectory tracking control problem for a differential wheeled mobile robot. The variable structure controller, based on the sliding mode theory, is a well known, proven control method, fit to deal with uncertainties and disturbances ( e.g., structural and parameter uncertainties, external disturbances and operating limitations). To minimize the problems found in practical implementations of the classical variable structure controllers, an adaptive fuzzy logic controller replaces the discontinuous portion of the control signals (avoiding the chattering), causing the loss of invariance, but still ensuring the robustness to uncertainties and disturbances without having any a priori knowledge of their boundaries. Moreover, the adaptive fuzzy logic controller is a feasible tool to approximate any real continuous nonlinear system to arbitrary accuracy, and has a simple structure by using triangular membership functions, a low number of rules that must be evaluated, resulting in a lower computational load for execution, making it feasible for real time implementation. Stability analysis and the convergence of tracking errors as well as the adaptation laws are guaranteed with basis on the Lyapunov theory. Simulation and experimental results are explored to show the verification and validation of the proposed control strategy. Abstract : Highlights: An adaptive fuzzy variable structure control integrated with a proportional plus derivative control is proposed. Trajectory tracking control for a differential wheeled mobile robot with robustness to uncertainties and disturbances without boundaries knowledge. The adaptive fuzzy variable structure control presents simple structure, making it feasible for real time implementation. The stability analysis and guarantee performed with basis on the Lyapunov theory and experimental results presented.